Juridical Review of Credit Agreements with Guarantees of Rights to Privately Owned Land to Plecit/Mobile Banks - Dany Zain Abdillah; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2023)
Loans that use Collateral using Land Objects Certificate of Ownership to Bank Plecit / Mobile Bank are a small example of the impact Economic development in Indonesia after the fall of the new order underwent significant changes and changes uncertainly. In this study, researchers used this normative research method which is qualitative and in this research method is more directed to the legal norms contained in various laws and regulations. and what is often used in this research method is for example examining the implementation of agreements in credit, in another sense The research method is a study that is quite in‐depth and full of calculations and caution from everything. Then the purpose of the researcher in this case is to study and analyze the validity of a land security that is not based on the debtor's property rights in credit agreements. According to the big dictionary, Indonesian the definition of a plecit bank or mobile bank is a reference to one person or non‐bank institution that lends money with a very high interest agreement, then for the collection system it is carried out every day by the account officer, land rights guarante that are not based on the debtor's property rights in the credit agreement and its legal consequences based on Law Number 4 of 1996 concerning Dependent Rights. By providing legal understanding, the community is expected to understand what they can do and apply in the future if there are agreements or cases related to credit with property certificate guarantees, which may result in violence in collection carried out by plecit banks, So that people become victims and perpetrators, can avoid violence. In this case, the property rights holder who makes the land certificate an object of guarantee to the plecit bank can issue a certificate because there is no APHT made by the PPAT party and there is no strong legal clarity from the plecit bank / mobile bank itself.